Return to Work and Work Productivity During the First Year After Cancer Treatment - So, Serana Chun Yee; Ng, Danielle Wing Lam; Liao, Qiuyan; Fielding, Richard; Soong, Inda; Chan, Karen Kar Loen; Lee, Conrad; Ng, Alice Wan Ying; Sze, Wing Kin; Chan, Wing Lok; Lee, Victor Ho Fun; Lam, Wendy Wing Tak (Frontiers in Psychology, 2022)
Objectives: Working-age cancer patients face barriers to resuming work after treatment completion. Those resuming work contend with reduced productivity arising from persisting residual symptoms. Existing studies of return to work (RTW) after cancer diagnosis were done predominantly in Western countries. Given that employment and RTW in cancer survivors likely vary regionally due to healthcare provision and social security differences, we documented rates and correlates of RTW, work productivity and activity impairment among Chinese cancer survivors in Hong Kong at one-year post-treatment. Methods: Of 1106 cancer patients assessed at six months post-cancer treatment (baseline), 593 previously worked; and detailed work status, psychological distress (HADS), physical symptom distress (MSAS-SF), supportive care needs (SCNS-SF34-C), health related quality of life (SF12), and illness perception (B-IPQ) were assessed. Six-months later (follow-up), work productivity and activity impairment were assessed (WPAI) (n=402). Descriptive analyses examined RTW rate. Fully-adjusted regressions determined RTW, work productivity and activity impairment predictors. Results: At baseline, 39% (232/593) were working, 26% (153/593) on sick leave, and 35% (208/593) were unemployed. Compared to patients returning to work, unemployed participants were older, likely manual/service-oriented workers, and had lower family income, chemotherapy, fewer unmet health system and information needs, poorer physical functioning and negative illness perceptions. Sick leave participants were likely service-oriented workers, who had head and neck cancer, chemotherapy, and poor physical functioning. At FU, baseline depressive symptoms, physical symptom distress, and negative illness perceptions predicted presenteeism and work productivity loss; gynaecological cancer, fewer unmet health system and information needs, and greater unmet sexuality needs predicted absenteeism; physical symptom distress, negative illness perception and poor physical functioning predicted activity impairment. Conclusions: Cancer survivors who had more physically-demanding jobs and poorer physical functioning delayed RTW. Unmanaged physical symptom and psychological distress hindered work productivity.